Air pollutant dispersion around high-rise buildings due to roof emissions. (1st July 2022) - Guo, Guang Ze; Yu, Yong; Kwok, K.C.S.; Zhang, Yu
Abstract: Air quality in the built environment has a significant impact on public health, particularly in densely populated cities where residents live in closely-packed high-rise buildings. In this case, communicable respiratory diseases are apt to spread through vent pipe emissions on the building roof and facilitate community transmission. This study applied computational fluid dynamics to simulate the dispersion of the pollutants discharged from the roof vent pipes around high-rise buildings. The results show that the dispersion process is dominated by wind-structure interaction, wind incidence angle, air pollutant discharge location, and vent pipe height, and the dispersion is more complex around crucifix-form buildings than cubic ones. When the wind incidence angle reaches around 90°, the air pollutants are entrained in the re-entry of the building, thus impeding the dispersion process. The building areas most adversely affected by air pollutants are located on high floors near the vent pipe. Changing air pollutant discharge location and increasing the height of the vent pipe can significantly reduce the affected area. Where the height of the vent pipe is restricted, parapets at the roof edges are suggested to further reduce the adverse effects of air pollutants. These research findings can help to reduce the risk of airborne contaminants/diseases spreading in current and future built environments. Highlights: The effects of wind-structure interaction on the dispersion of rooftop vent pipe discharge from a cubic and a crucifix form building were investigated. Proper vent pipe position and height reduce the adverse effects of the area around the building affected by the air pollutants discharged from the vent pipe. Parapets of the building roof can further reduce the adverse effects of the air pollutants discharged from the vent pipe.